Comparative Effectiveness of Cheonwangbosimdan (Tian Wang Bu Xin Dan) Versus Cognitive-Behavioral Therapy for Insomnia in Cancer Patients: A Randomized, Controlled, Open-Label, Parallel-Group, Pilot Trial. (July 2020) - Moon, Sun-Young; Jerng, Ui Min; Kwon, O-Jin; Jung, So-Young; Lee, Jee Young; Yoon, Seong Woo; Shin, Won-Chul; Byun, Jung-Ick; Lee, Jun-Hwan
Cancer patients have a 2 times higher prevalence of insomnia than healthy populations and cancer-related insomnia has received minimal attention while insomnia can aggravate the rehabilitation of cancer patients. Cheonwangbosimdan is a Korean herbal medicine generally used to relieve sleep deprivation, however, few studies presented the effects of Cheonwangbosimdan on cancer-related insomnia. The purpose of study is to examine the feasibility of Cheonwangbosimdan treatments for cancer patients. Twenty-two participants were allocated into a Cheonwangbosimdan or cognitive-behavioral therapy for insomnia (CBT-I) control group by equal number. The intervention group took Cheonwangbosimdan liquid once in a day and attend visits once a week for 4 weeks. The CBT-I group underwent individualized behavioral therapy 4 times in 4 weeks. The primary outcome is changes in the Insomnia Severity Index (ISI) from baseline to the end of the trial. Responses to the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Zung Self-Rating Anxiety Scale (SAS), Brief Fatigue Inventory (BFI), Euroqol-5 Dimensions-5 Levels (EQ-5D-5L), and Eastern Cooperative Oncology Group Performance Status (ECOG-PS) were secondary outcomes used to evaluate the quality of sleep. Outcomes were measured at a follow-up visit (visit 5) in the fifth week of the trial. There is no difference between 2 groups, but both groups showed tendency to alleviate cancer insomnia symptoms. SAS-K showed significant difference between the 2 groups (P < .001), as treatment group score was highly lowered than control group score. The study can contribute to more attentive care for insomnia in cancer patients.